An unplanned life a memoir - Elsey, George M., 1918-; ebrary, Inc. (Columbia : University of Missouri Press, 2005)
"Memoir of the author's experiences working in the White House during the Roosevelt and Truman administrations, including inside accounts of his work on classified documents, U.S.-Soviet relations, and Truman's "Whistle-Stop Campaign," and his long association with the American Red Cross"--Provided by publisher.
From Oakmont to ONI -- The Map Room -- Normandy -- Back to the White House -- A new president -- Into everything -- 1948 -- "A passion for anonymity" -- Korea -- Sally, Averell, and the Red Cross -- Pullman and the Pentagon -- Capstone.
Includes index.
Electronic reproduction.
Keywords: Elsey, George M., -- 1918-; Roosevelt, Franklin D. -- 1882-1945.; Truman, Harry S., -- 1884-1972.; American Red Cross -- History -- 20th century; Political consultants -- United States -- Biography; Presidents -- United States -- Staff -- Biography; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- Soviet Union; United States -- Politics and government -- 1933-1945.; United States -- Politics and government -- 1945-1989.; Electronic books